Effect of some plants on the growth and content of leaves of chlorophyll and water for two varieties of wheat - Mohammed Fasel; Ghazwan Hassan; Alaa Al-Shallal (College of Education for Pure Sciences, 2007)
The present study was carried out in green house to detect the allelopathical effects of roots and shoots residues for (Foeniculum vulare and Medicago sativa) with added to the soil at the ratio 2.5o/o and 5% W: W mixed and incubated for 3 weeks on growth of two wheat cultivars. The results show addition residues root and shoot both plants with concentration 2.5o/o and 5% caused inhibition of growth two wheat cultivars through effect on some characters (plant height, leaf area, chlorophyll content and relative water content) compared with the plants that grown in control soil (without residues). On the other hands the cultivar Abu Graib-3 was better than Shaam-1 in the most characters studied and more resistant to allelopathic effect of these residues.